Platform independent tool for local event correlation - Vaarandi, Risto (Acta Cybernetica, 2002)
Event correlation plays a crucial role in network management systems, helping to reduce the amount of event messages and making their meaning clearer to a human operator. In early network management systems, events were correlated only at network management servers. Most modern network management systems also provide means for local event correlation at agents, in order to increase the scalability of the system and to reduce network load. Unfortunately all event correlation tools currently available are commercial, quite expensive, and highly platform dependent. The author presents a free platform independent tool called sec for correlating network management events locally at an agent's side.